Robert Mugabe's 2013 presidential election campaign - Tendi, M (Routledge, 2013)
Zimbabwe staged harmonised presidential, parliamentary and local elections on 31 July 2013. I was in Zimbabwe from 2 July to late September. Throughout this period, I closely followed the political fortuna of Zimbabwe President Robert Gabriel Mugabe before and after the 31 July presidential election. I had unique access to Mugabe’s campaign managers and was allowed to observe his electioneering at close range. Thus, the following account is based on first-hand knowledge of Mugabe’s election campaign. I have interviewed Zimbabwe African National Union (Patriotic Front) (ZANU[PF]) and military elites frequently since 2010 as an independent researcher. Through this constant interaction I have developed a good degree of trust and understanding with some of my research subjects, which has enabled me to secure access. My account focuses on five themes: Mugabe’s state of mind and authority ahead of the election; his campaign message; political violence; the cohesion of Mugabe’s ZANU(PF)party; and campaign funding. I contend that the views of a number of academics, rival politicians and sections of local and international media during the campaign period that Mugabe was no longer the authoritative figure within his party and over the military and that he had lost much of his physical and mental powers were misleading. ‘Patriotic history’ and a narrative about the importance of peace during the campaigns, the benefits of ZANU(PF)’s Fast Track Land Reform programme, and a pledge to fully indigenise and economically empower the generality of Zimbabweans were Mugabe’s key campaign messages. Mugabe’s campaign was slick, well-funded, united and peaceful, in contrast to his 2008 presidential election campaign, which was underfunded, plagued with internal division and characterised by extreme violence in the June run-off. This article attempts to account for some of these changes and continuities, in addition to offering a perspective on his electioneering in July 2013.